Analysis of distress in patients undergoing radical prostatectomy: A multicenter prospective study - Duk Yoon Kim; Jae Hyun Ryu; Tag Keun Yoo; Yun Beom Kim; Tae Young Jung; Woo Jin Ko; Eun Kyoung Yang (Investigative and Clinical Urology, 2024)
Purpose: To analyze the degree of psychological distress experienced pre- and postoperatively in patients who underwent radical prostatectomy after being diagnosed with prostate cancer. Materials and Methods: Patients diagnosed with prostate cancer who underwent radical prostatectomy without history of psychiatric disorders were included in this study. The degree of psychological distress was evaluated using hospital anxiety and depression scale (HADS) and distress thermometer (DT) questionnaires preoperatively and at 1, 3, 6, and 12 months postoperatively. Results: Distress was high preoperatively and decreased over the entire period. In addition, HADS-anxiety and HADS-depression scores showed an improved severity, shifting from an abnormal state to a borderline state in some patients. However, the DT score, including emotional problems, spiritual concerns, physical problems, family problems, and practical problems, was slightly higher at 1 month postoperatively compared to preoperatively. Furthermore, even at 12 months postoperatively, about one fifth of patients surveyed had a DT score of 4 or higher, requiring psychiatric intervention. Conclusions: Before and after radical prostatectomy, a significant number of patients complained of distress such as anxiety, depression, and insomnia, and they needed help from a specialist because of psychological distress even 12 months postoperatively. Therefore, a close evaluation of the patient’s psychological distress and supportive treatment are needed during the entire pre- and postoperative period.